1999
DOI: 10.1007/s100520050388
|View full text |Cite
|
Sign up to set email alerts
|

Annihilation, glueball and flavor mixing effects in pseudoscalar mesons

Abstract: The pseudoscalar mesons η(547), η (958) and η (1410) are studied in the gluonium-quarkonium mixing framework. The SU(3)-flavor symmetry breaking and annihilation effects are considered. Estimates of the glueball mass and of the ms/mu ratio are provided. The system η(1295) and η( 1490) is also considered in a mixing scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 16 publications
(34 reference statements)
2
16
0
Order By: Relevance
“…In the study of [37] it has been found that η(1295) is most likely (ūu +dd)/ √ 2, while η(1490) is almost puress state. Therefore, we might expect the presence of η(1490) in the diagram A 1−2 .…”
Section: The Modelmentioning
confidence: 99%
“…In the study of [37] it has been found that η(1295) is most likely (ūu +dd)/ √ 2, while η(1490) is almost puress state. Therefore, we might expect the presence of η(1490) in the diagram A 1−2 .…”
Section: The Modelmentioning
confidence: 99%
“…The theoretical and experimental results are compared in Table 1. These results show that the quarkonium-gluonium mixing model, which works well for scalar isosinglet mesons [10], is not compatible with the constraints coming from decays concerning the axial and tensor isosinglet mesons considered in this work.…”
Section: Discussionmentioning
confidence: 51%
“…In the pseudoscalar sector [10] the value of m G was limited to the interval between the masses of the pseudoscalar mesons η and η ′ , in order to keep the mass matrix Hermitian, because outside this interval Λ g becomes a complex number. For a given value of m G the parameter ε is determined by the minimum of m s /m u , consistent with the usual values in the nonrelativistic constituent quark models, which are in the range 1.3 − 1.8.…”
Section: The Mass Matrix Formalismmentioning
confidence: 99%
See 2 more Smart Citations